Experimental and human population studies of DNA lesions in healthy individuals - Sjakste, N. (Вiopolymers and Cell, 2017)
DNA damage is a valuable biomarker in human molecular epidemiology being associated with many diseases. However, the level of DNA damage is influenced also by intrinsic features of healthy individuals: heredity, sex, age and body type. This review summarizes data on DNA breakage level in healthy humans depending on their characteristics and compares these data with experimental studies and observations on animals. Several strains of laboratory animals manifest an increased level of DNA breaks. In humans, some gene polymorphisms are associated with an increased level of DNA damage; however it is believed that environmental factors are more important. In animals, a higher level of DNA breakage is usually detected in males. In humans, data on the role of gender are contradictory and depend on origin. Experimental models provide evidence of increased levels of single- and double-strand breaks in obese animals. Although human studies are less convincing, an increase of double-strand breaks appears to be a more reproducible feature of DNA of overweight persons. Data on single-strand DNA breaks in aged persons are contradictory, but double strand breaks evidently increase with age. Пошкодження ДНК є інформативним біомаркером для молекулярної епідеміології, так як вони пов'язані з багатьма захворюваннями людини. У той же час рівень пошкоджень ДНК може залежати від внутрішніх властивостей притаманних здоровим людям: спадковості, статі, віку і статури. Метою даного огляду є узагальнення даних щодо розривів ДНК у здорових людей в залежності від їхніх характеристик у порівняння з даними експериментів і спостережень за тваринами. У лабораторних тварин кількох ліній спостерігають підвищений рівень розривів ДНК, у людини - кілька генних поліморфізмів асоційовані з підвищеним рівнем розривів, але вважається, що визначальними є зовнішні фактори. У самців тварин ДНК пошкоджена сильніше, ніж у самиць, дані по людині суперечливі і залежать від раси. Експериментальні моделі показують підвищений рівень одно- і дволанцюгових розривів ДНК при ожирінні. Дані досліджень на людині менш переконливі, краще відтворюються дані щодо підвищеного рівеня дволанцюгових розривів ДНК у людей із зайвою вагою. По одноланцюгових розривах ДНК при старінні дані суперечливі, переконливо показано зростання дволанцюгових розривів ДНК з віком. Повреждения ДНК являются информативным биомаркером для молекулярной эпидемиологии, так как они связа-ны со многими заболеваниями человека. В то же время уровень повреждений ДНК может зависеть от внутренних свойств, присущих здоровым людям, от наследственности, пола, возраста и телосложения. Целью данного обзора будет обобщение данных о разрывах ДНК у здоровых людей в зависимости от их характеристик и сравнение с данными экспериментов и наблюдений на животных. У лабораторныз животных нескольких линий наблюдают повышенный уровень разрывов ДНК, у людей несколько генных полиморфизмов ассоциированы с повышенным уровнем разрывов, но считается, что определяющими являются внешние факторы. У самцов животных ДНК по-вреждена сильнее, чем у самок, данные по людям противоречивы и зависят от расы. Экспериментальные модели указывают на повышеннй уровень одно- и двунитевых разрывов ДНК при ожирении. Данные исследований на людях менее убедительны, лучше воспроизволдятся данные, указывающие на повышенный уровень двунитевых разрывов ДНК у людей с лишним весом. Данные по однонитевым разрывам ДНК при старении противоречивы, убедительно показано нарастание двунитевых разрывов ДНК с возрастом.